'A Pint of These Maiden Cuthburga Oats': The Cult of St Cuthburga at Thelsford Priory, Warwickshire, October 1538. (3rd July 2017) - Cornish-Dale, Charles
Abstract : This article concerns the only other known late-medieval cult of St Cuthburga outside Wimborne Minster, Dorset. John London, one of the commissioners for the dissolution of the monasteries, encountered an image of the saint at a Trinitarian priory in Warwickshire, in 1538. How did the cult of this obscure Wessex saint end up in the heartlands of Mercia? And what might the transmission of this cult tell us, not only about the Trinitarians – an international religious order about whose place in the late medieval English scene little is known – but also about the nature of popular devotion more generally?